2003
DOI: 10.1148/radiol.2272020455
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Features of Self-limiting Adult Small-Bowel Intussusception Identified at CT

Abstract: Intussusception length is the main factor in distinguishing the majority of small-bowel intussusceptions detected at CT that are self-limiting from the minority that require surgery. An intussusception that is shorter than 3.5 cm is likely to be self-limiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
112
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 14 publications
6
112
0
8
Order By: Relevance
“…Given this increased detection of intussusception, even in asymptomatic patients, and given the recognition that some may be transient, there is an ongoing controversy regarding the optimal management of these cases. The general consensus is that proximal small-bowel intussusceptions measuring less than 3.5 cm in length and without obstruction or an obvious lead point are likely to be selflimiting and of no clinical significance [30], and larger sections should be monitored conservatively [31], only resorting to surgery if complications arise.…”
Section: Discussionmentioning
confidence: 99%
“…Given this increased detection of intussusception, even in asymptomatic patients, and given the recognition that some may be transient, there is an ongoing controversy regarding the optimal management of these cases. The general consensus is that proximal small-bowel intussusceptions measuring less than 3.5 cm in length and without obstruction or an obvious lead point are likely to be selflimiting and of no clinical significance [30], and larger sections should be monitored conservatively [31], only resorting to surgery if complications arise.…”
Section: Discussionmentioning
confidence: 99%
“…However, radiologic findings of intussusception on CT, except in infants, do not warrant surgical intervention in many cases, as mentioned in some reports [7][8][9]. According to a recent study [7], only 15% of adult intussusceptions found on imaging studies were intussusceptions with lead points verified on exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Intussusception of length that is less than 3.5cm is predictive of spontaneous resolution; hence it is likely to be self-limiting and not requiring surgery. 22 Lvoff et al has concluded that due to increased detection of selflimiting small bowel intussusception with CT scans, it is important to note that intussusception with length of less than 3.5cm is more likely to be self-limiting and not requiring surgery. 22 In the presence of a coexisting surgical pathology, surgical resection is usually indicated, with frozen section of the specimen obtained to exclude malignancy.…”
Section: Management Of Retrograde Intussusceptionmentioning
confidence: 99%
“…22 Lvoff et al has concluded that due to increased detection of selflimiting small bowel intussusception with CT scans, it is important to note that intussusception with length of less than 3.5cm is more likely to be self-limiting and not requiring surgery. 22 In the presence of a coexisting surgical pathology, surgical resection is usually indicated, with frozen section of the specimen obtained to exclude malignancy. 23,24 In retrograde intussusception, spontaneous resolution is more likely due to antegrade peristalsis, which accounts for the resolution of intussusception in our patient during laparotomy.…”
Section: Management Of Retrograde Intussusceptionmentioning
confidence: 99%